Persistent Rhesus Enteric Calicivirus Infection in Recombinant CHO Cells Expressing the Coxsackie and Adenovirus Receptor - Tibor Farkas; Zeinab R. Aboezz (Viruses)
Recently, using a panel of recombinant CHO cell lines, we identified the coxsackie and adenovirus receptor (CAR) and histo-blood group antigens (HBGAs) or sialic acid as the minimum requirement for susceptibility to rhesus enteric calicivirus (ReCV) infections. While ReCVs cause lytic infection in LLC-MK2 cells, recombinant CHO (rCHO) cell lines did not exhibit any morphological changes upon infection. To monitor infectious virus production, rCHO cell cultures had to be freeze–thawed and titrated on LLC-MK2 monolayers. This raised the question of whether ReCV infection in rCHO cells is persistent and whether non-enveloped progeny virions are released from the infected cells. Here, we used the rCHO-CAR+ cell line and a CAR and sialic acid-dependent recovirus strain (FT7) and found that these cells were persistently infected, and infectious virus was continuously produced and released into the culture without showing any visible cell damage. Viral capsid protein and replication intermediate double-stranded RNA (dsRNA) were detectable in almost all cells for at least 12 passages. We suspect a fully exosomal viral exit mechanism without a lytic cycle in these cells. rCHO cell may provide a valuable system for ReCV production (producer cell line) and serve as a model for investigating enteric calicivirus non-lytic viral exit mechanisms and the properties of the released, most likely membrane-cloaked, infectious progeny virions.